Behavior of silica mesoporous materials for capacitive deionization desalination - Fatemeh Hemmati Tirabadi; Ramin M.A.Tehrani; Leila Hajiaghababaei; Alireza Badiei; Afsane Mollahosseini (Scientific Reports)
Abstract In the present study, mesoporous silica with a high specific surface area (about 1365 m2/g), pore size (5.96 nm), and excellent hydrophilic surface was used as an electrode in capacitive deionization (CDI). Characterization of the structure and morphology of the fabricated materials was collected by Fourier Transform Infrared Spectroscopy, contact angle, Brunauer–Emmett–Teller, Scanning electron microscopy, Thermogravimetric Analysis, and X-ray diffraction. The electrochemical properties of mesoporous silica were assessed by electrochemical impedance spectroscopy and cyclic voltammetry tests. As a result, mesoporous silica presented a high specific capacitance of 495 F/g. Furthermore, the influence of mesoporous silica electrodes on desalination performance in a NaCl solution (200 mg/L) at 1.2 V was studied. The introduced mesoporous silica showed an excellent salt adsorption capacity of 22.78 mg/g in the CDI cell. Also, the present study investigated the influence of pore size and hydrophilic groups on desalination performance. The results exhibited that the synthetic-mesoporous silica is a powerful potential electrode material for CDI and can be applied for saline water deionization.